BMS service sector management 3rd year 5th semester - Patankar S.V., Erande A.V., Tare T.S. and others (Sheth Pub., Mumbai, 2005)
B.M.S.
ENGLISH
Keywords: BMS service sector management 3rd year 5th semester; B.M.S.; B.M.S.